Spatiotemporal drought characteristics during growing seasons of the winter wheat and summer maize in the North China Plain - Li, Qing; Liu, Yun; Luo, Lanyang; Wang, Yu; Wang, Qian; Ma, Meihong (Frontiers in Earth Science, 2024)
The North China plain (NCP) is an important production base for winter wheat and summer maize in China. Severe droughts seriously restrict agricultural production in this region, threatening food security. Based on the standardized precipitation evapotranspiration index (SPEI), this study explored the spatial and temporal drought characteristics during the winter wheat and summer maize growing seasons in the region. The study found that: (1) From 1980 to 2013, the drought trend of the winter wheat growing season in the NCP has intensified, with Huang-Huai Plain agricultural area (HH_P) showing the most significant drought trend. However, the summer maize growing season has become wetter, with the Shandong hilly agricultural and forestry area (SD_Q) showing the most significant wetting trend. (2) After the year 2003, the results from Mann-Kendall trend analysis revealed that the drought trend of HH_P during the winter wheat growing season became particularly pronounced, but the wetting trend of SD_Q and HH_P during the summer maize growing season became more evident. (3) The dominant spatial patterns observed in the NCP during the growing seasons of winter wheat and summer maize were marked by a consistent distribution of drought and wetness conditions. For winter wheat, the southern regions of the foothill plain area of Yanshan and Taihang Mountains (YT_P) and the low-lying plain area of Hebei, Shandong, and Henan (JLY_P) were more sensitive to the changes of drought and wet conditions. For summer maize, SD_Q was more sensitive to the changes of the drought and wet conditions. The results of this study could provide references for the formulation of drought relief strategies of winter wheat and summer maize in the NCP.